2016
DOI: 10.1007/s12199-016-0540-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of A-21T and C-262T genetic polymorphisms at the promoter region of the catalase (CAT) on gene expression

Abstract: The present findings indicated that these polymorphisms were significantly associated with the gene expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 27 publications
2
13
0
1
Order By: Relevance
“…The PAX-6 is a highly conserved multifunctional transcription factor that takes part actively in the development of the eye and brain, and it has been proposed to bind to the promoter region of CAT gen to regulate its expression. Directly in line with previous data mentioned, Saify et al [ 41 ] identified the mRNA gene expression of CAT from peripheral mononuclear cells stratified by AA, AT, and TT genotype of − 21A>T CAT (rs7943316) polymorphism. A significant positive correlation was observed between the mRNA level expression of CAT by mononuclear cells and the presence of thymine allele.…”
Section: Discussionsupporting
confidence: 77%
“…The PAX-6 is a highly conserved multifunctional transcription factor that takes part actively in the development of the eye and brain, and it has been proposed to bind to the promoter region of CAT gen to regulate its expression. Directly in line with previous data mentioned, Saify et al [ 41 ] identified the mRNA gene expression of CAT from peripheral mononuclear cells stratified by AA, AT, and TT genotype of − 21A>T CAT (rs7943316) polymorphism. A significant positive correlation was observed between the mRNA level expression of CAT by mononuclear cells and the presence of thymine allele.…”
Section: Discussionsupporting
confidence: 77%
“…126). Higher activity was showed for the CC genotype [ 8 ]. This variation alters the binding of transcription factors, and thus affects on the basal expression as well as blood catalase activity.…”
Section: Discussionmentioning
confidence: 99%
“…GPx1 rs1050450 polymorphism causes a proline-leucine substitution at codon 198, which correlated with lipid peroxidation, GPx1 activity and breast cancer risk [19]. C-262T polymorphisms at CAT affected its expression in cells and serum level [20,21]. Previously, we reported SOD2 rs4880, which may regulate SOD2 catalyzation activity, could predict gastric patients' survival after receiving adjuvant chemotherapy [22].…”
Section: Introductionmentioning
confidence: 99%